Extracellular Matrix Remodeling and Its Role in Myocardial Regeneration Following Infarction - Sullivan, Kelly. (2017)
Abstract: The extracellular matrix is no longer considered a static support structure for cells, but a dynamic signaling network with the power to influence cell, tissue and whole organ physiology. In the myocardium, the synthesis, deposition and degradation of matrix proteins are critical for the development and maintenance of functional heart tissue as well as the stabilization of the organ following injury. However, the extent to which the extracellular matrix is remodeled during disease progression is often excessive and greatly impacts heart functionality as well as the efficacy of therapeutic intervention. Therefore, it is critical to specifically characterize how the biophysical and biochemical properties of the extracellular matrix are altered as a function of time following the onset of disease in order to better understand the challenges associated with repairing the injured myocardium. The application of decellularization to study alterations in the extracellular matrix of disease tissue as a function of time following injury was first explored by our research group. This technique enabled us to specifically characterize how the remodeled ECM impacts the regenerative potential of mesenchymal stem cells and more specifically, how the chronic infarct ECM promotes pro-survival paracrine signaling to oxidatively stressed cardiomyocytes in vitro. Furthermore, the use of non-linear optical microscopy enabled us to identify how the structure function relationships of the myocardial ECM change following infarction due to the non-destructive imaging techniques of second harmonic generation and two photon excited fluorescence. In particular, this work highlighted how the ECM deposited following infarction is structurally immature relative to its native state, with dense, but thin collagen fibers that lack cross-links and therefore possesses a reduced elastic modulus. Incorporation of this remodeled ECM into a complex disease model platform which describes differences in oxygen tension, immunomodulatory cytokines, matrix composition and the mechanical properties of the ECM following MI induction, enabled us to predict cardiac progenitor cell fate following intramyocardial delivery. The results highlighted how the cytotoxicity of the infarct microenvironment impedes vascular differentiation and how the variability of progenitor cell isolates and their individual sensitivities to infarct variables necessitates the selection of an implantation strategy, which is beneficial for a particular patient's population of cells. Finally, the incorporation of ECM derived from both fetal and adult developmental stages into a silk scaffold for cardiac regeneration following myocardial infarction highlighted how the specific composition of the ECM regulates the therapeutic efficacy of the biomaterial by impacting host cell migration, infiltration and remodeling. The research described in this thesis highlights the importance of characterizing the extracellular matrix throughout development and disease in order to fully understand its impact on organ function, disease progression and therapeutic intervention.; Thesis (Ph.D.)--Tufts University, 2016.; Submitted to the Dept. of Biomedical Engineering.; Advisor: Lauren Black.; Committee: David Kaplan, Gordon Huggins, and Michael Davis.; Keyword: Biomedical engineering.